Comparative evaluation of fragment reattachment protocols for the management of teeth with crown‐root fractures. Issue 4 (12th March 2022) - Lokade, Amolkumar; Tewari, Nitesh; Goel, Shubhi; Mathur, Vijay Prakash; Srivastav, Sukeshana; Rahul, Morankar
Abstract: Background/Aim: A crown‐root fracture is a fracture of both the crown and the root of a tooth. The International Association of Dental Traumatology (2020) guidelines recommended fragment reattachment and stabilization of loose fragments as an immediate management protocol for uncomplicated crown‐root fractures. However, the lack of evidence and unpredictability make it a less popular treatment option. The aim of this study was to compare three protocols of fragment reattachment for the management of teeth with crown‐root fractures. Methodology: Eighty mandibular bovine incisors with similar dimensions and no structural deformities were selected and randomized into four groups: Group I (Control/sound teeth); Group II (no rehydration); Group III (rehydration in distilled water for 15 min) and Group IV (rehydration in a humidification chamber for 15 min). A fracture was simulated to extend from the labial side of the middle‐third of the crown to the palatal side of the cervical‐third of the root. Fragments were exposed to the environment under normal temperature and pressure. Fragments were later reattached as per the standard protocol following the rehydration as specified for each group. Samples were subjected to thermocycling, and the force required to fracture them was evaluated by using a universal testing machine. Results: The highest mean force required to fracture was seen in Group IV (208.27 ± 75.99 N) followed by Group III (182.01 ± 90.13 N) and Group II (158.85 ± 68.04 N). These differences were statistically significant. Comparison of the mean difference of force required to fracture between pairs of groups revealed statistically significant mean differences only between the controls and each experimental group. Conclusion: The force required to fracture the reattached fragments in teeth with crown‐root fractures was affected by rehydration of the fragments. The force was higher in fragments reattached after rehydration, and the highest force was required in the teeth that had been rehydrated in a humidification chamber.